Learning creative writing in foreign language classes as a means of forming students’ communicative competence - Гладка, О. В. (Pedagogy of Higher and Secondary Education, 2012)
Gladkaya O. V. Learning creative writing in foreign language classes as a means of forming students’ communicative competence. The article deals with teaching creative writing at the English lessons as the means of forming students’ communicative competence. The notions «creative writing», «teaching creative writing» are concretized. The stages of its realization are singled out.